Strategi Harian Ambon Ekspres Dalam Memasarkan Ruang Iklan (Analisis Komunikasi Pemasaran) - La Hope, Aditha Wahyuni; Bandjar, Antasari (Jurnal Ilmu Komunikasi Pattimura, 2023)
This research is a qualitative descriptive study that aims to determine the marketing communication strategy applied by the Daily Ambon Ekspres in marketing its advertising space, including strategy analysis, marketing mix, and advertising space. The research was conducted at the Ambon Ekspres Daily Office in Ambon, Maluku. Primary data was collected through interviews with some informants involved in the advertising space marketing process. The informants are the Head of General Affairs and HR and the Head of Advertising and Promotion. The study result showed that the marketing communication strategy done by the Ambon Ekspres Daily in marketing its advertising space was by conducting collaborative activities with various stakeholders and also carrying out various forms of marketing mix such as through the marketing mix (4P) by Jarome McCarthy, which included product, price, place and distribution, and promotion. The promotion section consists of advertising, personal selling, public relations, sales promotion and direct marketing. Ameks also offers ads space containing display ads, classified ads, costum ads, and inserts. Ameks Daily’s strategy in the marketing advertising space is very good and in accordance with marketing communication theory.